Potret Insan Unggul Perspektif Al-Qur’an (Antara Postulat Al-Qur’an dan Harapan Pendidikan Islam) - Wahyudin Wahyudin; Nurlaelah Sultan (Universitas Muslim Indonesia, 2023)
Producing quality and superior human beings is always an interesting matter to study, so it often becomes a topic of discussion in various discussion forums and scientific meetings. To give birth to superior human beings, it cannot be separated from talking about human nature itself. Understanding the nature, nature and character of human beings is a strategic key in the effort to build